Effect of hydrate water on the hydrogen bond formation in dimethylaminoarglabine salts with hydrochloride and hydronitrate - Turdybekov, K.M.; Mustafin, E.S.; Turdybekov, D.M.; Adekenov, S.M. (Journal of Structural Chemistry, 2020)
The crystal structure of crystalline hydrates of dimethylaminoarglabine hydrochloride and dimethylaminoarglabine hydronitrate is determined by single crystal X-ray diffraction. It is established that in a crystal, water breaks the hydrogen bond between the anion and the cation in dimethylaminoarglabin hydrochloride and weakens it in dimethylaminoarglabin hydronitrate, which improves the solubility of salts in water.
Keywords: dimethylaminoarglabine hydrochloride; dimethylaminoarglabine hydrochloride hydrate; dimethylaminoarglabine hydronitrate hydrate; hydrogen bond